2020
DOI: 10.1186/s12933-020-01173-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on the early-phase arterial healing after drug-eluting stent implantation

Abstract: Background Early arterial healing after drug-eluting stent (DES) implantation may enable short dual-antiplatelet therapy (DAPT) strategy. The impact of diabetes mellitus (DM) on this healing has not been elucidated. We used coronary angioscopy (CAS) to compare intravascular status of DM and non-DM patients in the early phase after DES implantation. Methods This study was a multicenter retrospective observational study. We analyzed CAS findings of 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Early-stage arterial healing after DES-PCI makes short-term dual antiplatelet therapy (DAPT) possible. A study ( 18 ) used coronary angiography [coronary artery stenosis (CAS)] data to compare the intravascular status of T2DM patients ( n = 149) and non-T2DM patients ( n = 188) in the early post-DES-PCI period, and it found that 3–5 months after DES implantation, DM patients showed more uncovered stent wires than non-DM patients, suggesting that the recent ultrashort DAPT strategy may not be applicable to patients with concomitant T2DM. Meanwhile, new-onset T2DM [new onset of DM (NODM)] after DES-PCI is receiving increasing attention.…”
Section: Comorbid Features Of Type 2 Diabetes Mellitus and Myocardialmentioning
confidence: 99%
“…Early-stage arterial healing after DES-PCI makes short-term dual antiplatelet therapy (DAPT) possible. A study ( 18 ) used coronary angiography [coronary artery stenosis (CAS)] data to compare the intravascular status of T2DM patients ( n = 149) and non-T2DM patients ( n = 188) in the early post-DES-PCI period, and it found that 3–5 months after DES implantation, DM patients showed more uncovered stent wires than non-DM patients, suggesting that the recent ultrashort DAPT strategy may not be applicable to patients with concomitant T2DM. Meanwhile, new-onset T2DM [new onset of DM (NODM)] after DES-PCI is receiving increasing attention.…”
Section: Comorbid Features Of Type 2 Diabetes Mellitus and Myocardialmentioning
confidence: 99%
“…In the era of coronary stenting, even with standard medication therapy, including intensive statin, dual antiplatelet, and intensive glycemia-lowering, diabetes remains a risk factor for the poor prognosis of patients with CAD (16)(17)(18). Diabetes has long been considered a poor prognostic factor for angiographic and clinical outcomes after PCI (18,19). Previous studies have shown that diabetes increases the risk of the onset of MI or cardiac death in patients with established CAD (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The prothrombotic setting is promoted via several pathways, such as platelet hyperactivity, increased platelet aggregation, endothelial dysfunction, and elevated levels of multiple clotting factors [ 6 8 ]. Another mechanism that may increase stent thrombosis risk in diabetic patients is a reduction of early arterial healing, which leads to more uncovered stent struts [ 28 ] that were found to be associated with coronary stent thrombosis [ 29 ]. Furthermore, stent sizing and apposition may be suboptimal in patients with diabetes due to more diffuse and calcified coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%